ANALYSIS OF PRIMARY SCHOOL STUDENT SKILLS IN WRITING DESCRIPTIVE TEXTS - Daden Sopandi (IKIP Siliwangi, 2020)
The purpose of this study was to determine the ability of students to write descriptive texts. This study was designed as a descriptive quantitative study and was carried out in MI Malingping located in Sukabumi Regency. The number of samples in this study were 40 students. In this study, researchers used a writing test as a research instrument where students were asked to write descriptive texts based on the topics given to them. In this study, researchers analyzed 5 descriptive text components written by students such as content, organization, grammar, vocabulary and mechanics. From the results of the study, the researchers found that the average score of students in descriptive text writing was 51.87 and that meant their writing skills in descriptive text could be categorized at a low level.